Negotiating English-Only Ideology: Translanguaging and L1 Integration in a Multilingual Indonesian EFL Classroom - Raden Agus Budiharto; Yuliarsih; Devie Reztia Anjarani (LPPM Universitas PGRI Semarang, 2026)
This study examines translanguaging and first language (L1) integration in an English as a Foreign Language (EFL) classroom in Pamekasan, Madura, an underrepresented multilingual region of Indonesia. Although translanguaging is increasingly recognized as a resource in multilingual pedagogy, EFL policies and classroom practices in Indonesia often remain aligned with English-only ideology, creating tension between theory and practice. The study aimed to explore how translanguaging is enacted, how teachers and students perceive it, and what learning impacts emerge. Using a qualitative case study design, data were collected through classroom observations, teacher interviews, and student focus group discussions in a public junior high school. Findings show that translanguaging involving Madurese (L1), Bahasa Indonesia (L2), and English (L3) is naturally embedded in classroom interaction and used strategically to explain complex grammar, clarify tasks, and manage participation. Students drew on L1 and L2 to co-construct meaning, collaborate on problem-solving, and express understanding more confidently. Teachers perceived translanguaging as beneficial for comprehension, engagement, and anxiety reduction, yet remained cautious due to institutional pressure for English-only instruction. The results demonstrate significant cognitive benefits, specifically enhanced conceptual clarity and improved retention of specialized vocabulary, alongside affective gains such as increased learner agency and reduced communicative apprehension. The study underscores the necessity of legitimizing students' full linguistic repertoires and recommends greater policy alignment and teacher education to support context-responsive, inclusive EFL pedagogy.